From color to shape: ontogenetic shifts in traits of the freshwater crab Dilocarcinus pagei (Brachyura: Trichodactylidae) - da Silva, Alexandre R.; Nogueira, Caio S. [UNESP] (Canadian Science Publishing, 2023)
Crustaceans usually undergo a series of changes after the puberty molt. These changes are often associated with size increases in the body and in structures such as the abdomen and claws so that they can achieve higher reproductive fitness. These morphological changes allow the animal to fight, court, and signal for its conspecific with better performance. To compare ontogenetic changes, we used the freshwater crab Dilocarcinus pagei Stimpson, 1851 as a model. We analyzed differences in carapace and claw shape, force generation (via the apodeme area), morphological integration of claws, and color changes among demographic groups. Adult crabs had an increase in claw and carapace size followed by a shape change that makes the claws more robust. In addition, the animals changed from a dark brown coloration in juveniles to a dark red coloration in adult males, while adult females presented a dark red-brown coloration. Presumably, phenotypic changes may enhance crabs’ ability to obtain different food sources, as well as fight for sexual partners, and manipulate females during courtship. Color changes can be a strategy by which adult males can signal to females, while the dark brown coloration of juveniles can help in camouflage in the substrate.
Keywords: claws; Dilocarcinus pagei; geometric morphometrics; ontogeny; red crab